A Paraconsistent Decision-Making Method - Carvalho, Fábio Romeu de; Abe, Jair Minoro (Smart Innovation, Systems and Technologies, 2018)
This book presents a novel decision-making support system based on paraconsistent annotated evidential logic, which directly handles imprecise, incomplete and contradictory data. The authors offer insights into areas such as engineering and biomedicine, as well as related fields. Decision analysis is useful in making choices when the consequences of actions are uncertain, like in business administration, where it assists in making investment decisions, and in health care, Decision analysis is also valuable when the possible actions may lead to conflicting consequences. A fundamental tenet of decision analysis is that even though the available information is incomplete, a decision must be made. Thus, analyses often contain assumptions about or estimates of missing data. The contribution that this method can provide to professionals and companies has significant relevance in terms of the impact of information systems on productivity and quality of the companies; the lack of training companies for proper planning and management of information systems; and the need for interdisciplinary treatment of several sectors of almost all related scientific areas. This book is a valuable resource for professionals seeking a competitive edge in their performance. .